GC-MS Phytochemical Profiling, Antidiabetic, and Antioxidant Activities of Khaya senegalensis Stem Bark and Azadirachta indica Leaves Extracts in Rats - Ahmed, Rania Mustafa; Khalid, Asaad; Mohan, Syam; Yagi, Sakina; Saad, Hasseba Ahmed; Bayoumi, Nada Kamal; Ali, Amna; El-Sharkawy, Karam Ahmed; Alhazmi, Hassan A.; Albratty, Mohammed; Javed, Sadique A.; Sultana, Shahnaz; et al. (Journal of Spectroscopy, 2023)
This study was performed to evaluate phytochemical composition of Khaya senegalensis stem bark and Azadirachta indica leaf hydroethanolic (80%) extracts using GC-MS technique as a tentative identification method and screen for antioxidant and antidiabetic properties in Wistar rats. Diabetes was induced by intraperitoneal injection of alloxan (150 mg/kg·bw). Animals were divided into groups of six and treated by extracts (400 mg/kg·bw) for 28 days. The results compared with positive and negative control groups of animals. After treatment, blood samples were collected to determine the blood glucose level, lipid profile, liver and kidney function markers, and DPPH free radical scavenging activity was evaluated. Phytochemical investigations revealed that extracts were enriched with a wide range of secondary metabolites such as phenols, saponins, triterpenes, alkaloids, flavonoids, sterols, fatty acids, siloxane derivatives, and anthraquinones in diverse concentrations with reported antioxidant and antidiabetic properties. Biological screening results indicated that both extracts exhibited free-radical scavenging property in DPPH screening, and in that, K. senegalensis stem bark extract (91 ± 0.02%) showed greater reduction than A. indica leaf extract (55 ± 0.03%), with an IC50 of 0.023 ± 0.03 g/mL, which was lower than the reference drug propylgallate (0.077 ± 0.03 g/mL). Both the extracts remarkably reduced the blood glucose concentration in diabetic rats (p<0.05). However, A. indica leaf extract showed greater reduction (52%) than K. senegalensis stem bark extract (37%). Similarly, the cholesterol, LDL, triglyceride, total protein, albumin, urea, creatinine, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels decreased significantly (p<0.05), in comparison to diabetic control animals. However, the concentrations of HDL slightly increased. Overall, both extracts showed significant antidiabetic and antioxidant potential in diabetic rats. As oxidative stress is associated with the hyperglycemia, the antioxidant activity displayed by the extracts will provide additional benefits in the antidiabetic therapy.